Оптимальный анизотропийный регулятор на основе наблюдателя Люенбергера минимального порядка - Чайковский, М. М.; Курдюков, А. П. (Видавництво Львівської політехніки, 2011)
This paper considers the problem of synthesis of a reduced-order anisotropic optimal controller for the cases when some part of the measured output or the whole vector can be measured precisely. The reduced-order controller is constructed on the base of Luenberger minimum-order state estimator. The controller parameters are defined from a solution to some system of nonlinear matrix algebraic equations.
Keywords: линейные системы; случайные возмущения; норма; анизотропия; оптимизация; регулятор пониженного порядка